Molecular identification of old Hungarian apple varieties - Wichmann, B.; Galli, Zs.; Molnár, S.; Galbács, Zs.; Kiss, E.; Szabó, T.; L., Heszky (International Journal of Horticultural Science, 2007)
Altogether 40, mainly old Hungarian apple varieties were screened with six previously described microsatellite markers. A total of 71 polymorphic alleles were detected (average 11.8 alleles/locus) and the heterozygosity of markers averaged very high (0.8). The genetic variability among the genotypes proved to be so remarkable that as few as three markers from the applied six were enough to distinguish between the 40 varieties. This was also confirmed by the cumulative probability of obtaining identical allele patterns for two randomly chosen apple genotypes for all loci, which value was quite low: 2.53 x 10-5. The molecular identification of these genetically very different old apple genotypes could be very useful in future breeding programs.